Undescribed C-geranylflavonoids isolated from the fruit peel of Paulownia catalpifolia T. Gong ex D.Y. Hong with their protection on human umbilical vein endothelial cells injury induced by hydrogen peroxide. (February 2019) - Wang, Ying-Ai; Guo, Xing; Jia, Xian-Hui; Xue, Jing; Du, Hong-Fang; Du, Cheng-Lin; Tang, Wen-Zhao; Wang, Xiao-Jing; Zhao, Yun-Xue
Abstract: Six undescribed C-geranylated flavonoids, including five C-geranylflavanones named as paucatalinones F - J, one C-geranylflavonol named as paucatalinone K, along with seven known geranylated flavanones, were isolated from the fruit peel of Paulownia catalpifolia T. Gong ex D.Y. Hong. Their structures were elucidated distinctly according to their UV, IR, MS, NMR, and CD data. Among them, two compounds were substituted with unusual modified geranyl groups, namely paucatalinone F with an oxygenated cyclogeranyl substituent and paucatalinone H with a terminal pyranoid geranyl substituent. Furthermore, the protective effects on human umbilical vein endothelial cells (HUVECs) injury induced by H2 O2 were evaluated, and paucatalinone F showed the most potential activity. The bioactive results suggested that the geranyl substituent may be an important factor for restraining oxidative HUVECs damage and Paulownia C-geranylated flavonoids might have the potential for preventing cardiovascular complications. Graphical abstract: Highlights: Six undescribed C-geranylated flavonoids were isolated from Paulownia catalpifolia. Some C-geranylated flavonoids displayed favorable protective effects on HUVECs injury induced by H2 O2 . Paucatalinone F with an oxygenated cyclogeranyl substituent showed the most potential activity.